The Impact of Maternal Health on Neonatal Surgical Outcomes: A Retrospective Analysis - Chauhan, Satyendra Singh; Siddhanta, Shilpi; J. Mahil, J. Mahil; Mandal, Mita; Ullagaddi, Rajeshwari (Journal of Neonatal Surgery, 2025)
Background: Maternal health conditions significantly impact neonatal outcomes, particularly in neonates undergoing major surgical interventions. This study evaluates the association between maternal health factors, including Gestational diabetes mellitus (GDM), hypertensive disorders, anemia, and obesity, with neonatal surgical morbidity and recovery. Methods: A retrospective cohort study was conducted at Paras Hospital Panchkula, analyzing 500 neonates undergoing major surgical procedures. Maternal and neonatal health records were extracted from hospital databases. Statistical analysis, including multivariate logistic regression, and Kaplan-Meier survival analysis, was performed using SPSS 22.0 and R 4.2.2 to determine associations between maternal conditions and neonatal surgical outcomes. Inclusion criteria encompassed neonates undergoing gastrointestinal, cardiac, neurosurgical, and urological procedures. Exclusion criteria included neonates with incomplete medical records and multiple gestations. Results: Neonates born to mothers with GDM exhibited a significantly higher risk of surgical complications (OR = 2.5, 95% CI: 1.7-3.5, p = 0.001). Maternal hypertensive disorders were associated with prolonged NICU stays (16 days vs. 10 days, p = 0.002). Sepsis (19%), respiratory distress syndrome (22%), and surgical site infections (14%) were the most common postoperative complications. Kaplan-Meier survival analysis (p = 0.028) indicated lower survival rates in neonates with maternal risk factors, while ROC curve analysis (AUC = 0.82, p < 0.001) demonstrated strong predictive accuracy for neonatal morbidity. Conclusion: Maternal health conditions significantly influence neonatal surgical outcomes. GDM, hypertension, and anemia were major risk factors for increased morbidity, prolonged NICU stays, and higher readmission rates. Early maternal health optimization and prenatal interventions are crucial in reducing neonatal surgical risks and improving postoperative recovery.